Vibration sensitivity of human muscle spindles and golgi tendon organs - Fallon, James B.; Macefield, Vaughan G. (Muscle & nerve, 2007)
The responses of the various muscle receptors to vibration are more complicated than a naïve categorization into stretch (muscle spindle primary ending), length (muscle spindle secondary endings), and tension (Golgi tendon organs) receptors. To emphasize the similarity of responses to small length changes, we recorded from 58 individual muscle afferents subserving receptors in the ankle or toe dorsiflexors of awake human subjects (32 primary endings, 20 secondary endings, and six Golgi tendon organs). Transverse sinusoidal vibration was applied to the distal tendon of the receptor‐bearing muscle, while subjects either remained completely relaxed or maintained a weak isometric contraction of the appropriate muscle. In relaxed muscle, few units responded in a 1:1 manner to vibration, and there was no evidence of a preferred frequency of activation. In active muscle the response profiles of all three receptor types overlapped, with no significant difference in threshold between receptor types. These results emphasize that when intramuscular tension increases during a voluntary contraction, Golgi tendon organs and muscle spindle secondary endings, not just muscle spindle primary endings, can effectively encode small imposed length changes. Muscle Nerve, 2007